Increasing SMEs Productivity Through Digital Transformation Adoption of Software as a Service and Development of Entrepreneurial Attitudes - Endar Pradesa; Ratih Eka Sakti; Metha Aditya Putri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to test the influence digital transformation adoption of Software as a Service cloud accounting services and development of entrepreneurial attitude to productivity SMEs in Lubuklinggau as measured by indicators make transactions easier, speeds up transactions, providing additional profits when completing transaction, increase efficiency in do transaction For variables digital transformation, adoption of Software as a Service cloud accounting services. Planning indicators, beliefs, orientation on task, taking risk, leadership, And honesty For variables development of entrepreneurial attitude . As well as indicator efficiency, effectiveness, and economical for variables SMEs productivity. This research uses the Purposive Sampling method. Deep sample study was 37 respondent SMEs in Lubuklinggau. Data used in this research was primary data obtained from distribution questionnaire directly. This study used a quantitative approach. Analysis data was done using Smart PLS 3. The results of this study indicate that the effect of digital transformation adoption of Software as a Service cloud accounting services and the development of entrepreneurial attitudes on productivity of SMEs in Lubuklinggau influential positive. This study was expected can provide benefits for SMEs in Lubuklinggau with the digital transformation of adopting Software as a Service cloud accounting services so that realization enhancement productivity Which Good and develop attitude entrepreneurial with Good so that productivity increase with good too.